Pemimpin Ideal dalam Perspektif Syair Gundul-Gundul Pacul - Saputra, Muhammad Indra (Universitas Islam Negeri Raden Intan Lampung, 2016)
The diversity of ethnicity, tribe, politic, and economy often induces paradigm that only accentuate group or primordialism. These conditions make it is still to create an adjustment to the presence of new values. Hence, we need an ideal leader that is able to integrate those diversities and collect inspirations from the noble values of our archipelago and also the values of universal progress.In Gundul-Gundul Pacul rhyme is a rhyme that emerged in the 1400s popularized by Sunan Kalijaga which contains the deep philosophical meaning of characteristic a leaders. That rhyme is giving us an illustration of ideal leader that must have high integrity, fully trusted and uphold the honor.